The digital museum for the preservation of cultural heritage : a case of the Chinese “Qipao”. - Luo, Yanling. (2009)
The significance of cultural heritage is the knowledge about the historical and cultural background in the traditional values that have great influence on the world society throughout its history and today. Museums and libraries are both treasure houses of human history and knowledge, as well as a repository of massive cultural heritage. With the development of digital technology, digitalisation represented a remarkable technical achievement that results in more substantial impact on the cultural industries and brings benefits to preserve the information. The World Wide Web frees people from the constraint of physical location. It provides a powerful tool for the rapid gathering and dissemination of ideas and information over the world. With the increasing ubiquity of high-speed connections and the use of increasingly sophisticated Web technologies, Internet is no longer a place where visitors browse web pages that contain static content. Web 2.0 is replacing the traditional Web through inclusion of collaboration, discussions and ideas sharing among a great number of users. This new wave promises to facilitate the cultural institutions to explore new form of universal and dynamic accessibility. It provides a great platform in changing the face of museums into a new engaging approach. Unfortunately, the initiatives of adopting Web 2.0 technologies in current digital museums are still limited. It has resulted in a critical lack of competitive advantage in the needs of online interactive conversations with their visitors.